2009
DOI: 10.1186/1475-2867-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated derivatives of recombinant human arginase (rhArg1) for sustained in vivo activity in cancer therapy: preparation, characterization and analysis of their pharmacodynamics in vivo and in vitro and action upon hepatocellular carcinoma cell (HCC)

Abstract: Background: Protein used in medicine, e.g. interferon, are immunogenic and quickly broken down by the body. Pegylation is a recognized way of preserving their integrity and reducing immune reactions, and works well with enzymes used to degrade amino acids, a recent focus of attention in controlling cancer growth. Of the two arginine-degrading enzymes being explored clinically, arginine deiminase is a decidedly foreign mycoplasm-derived enzyme, whereas human arginase 1 is a native liver enzyme. Both have been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Thus, normal cells which lack OTC can become toxic while tumor cells which lack both ASS and OTC are more sensitive [36]. Nevertheless, its pegylated and modified form to improve activity and pharmacokinetic profile has been synthesized [37, 38] in preparation for clinical trial. Another factor which influences the response to arginine deprivation is autophagy which enables melanoma cells to survive and hence combination treatment is needed to enhance the apoptotic signal.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, normal cells which lack OTC can become toxic while tumor cells which lack both ASS and OTC are more sensitive [36]. Nevertheless, its pegylated and modified form to improve activity and pharmacokinetic profile has been synthesized [37, 38] in preparation for clinical trial. Another factor which influences the response to arginine deprivation is autophagy which enables melanoma cells to survive and hence combination treatment is needed to enhance the apoptotic signal.…”
Section: Discussionmentioning
confidence: 99%
“…interferon, are immunogenic and they are quickly broken down by the body. PEGylation is a recognized way of preserving their integrity and reducing immune reactions, and works well with enzymes used to degrade amino acids, a recent focus of attention in cancer therapy [12]. Several other products including pegvisomant and certolizumab pegol have also proven to be effective and they are in high demand [10].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ammonia levels may be toxic in vivo [17]. Pegylated recombinant human arginase [ArgI (Mn)-PEG5000] metabolizes arginine to ornithine and urea and has shown antitumor activity in vitro and in vivo [15,[18][19][20][21]. However, past studies have found that the HuArgI (Mn)-PEG5000 enzyme is unstable in serum and displays low catalytic activity at physiological pH [22].…”
Section: Introductionmentioning
confidence: 99%
“…Pegylated recombinant arginine deiminase (ADI-PEG20) degrades plasma arginine to citrulline and ammonia, but it is immunogenic [14][15][16]. One drawback of ADI-PEG20 is onset of hyperammonemia, which was reported in 5.9% of patients at a dose of 320 IUm -2 [16].…”
Section: Introductionmentioning
confidence: 99%